Erythrokeratoderma en cocardes - A rare phenotype - P Arunprasath; Reena Rai; G Umamaheswari (Wolters Kluwer Medknow Publications, 2020)
Erythrokeratodermas are disorders of keratinization with two major types, namely erythrokeratodermia variabilis and symmetrical progressive erythrokeratoderma. Apart from the two main types, rare variants include erythrokeratoderma en cocardes (EEC), erythokeratoderma with erythema gyratum repens-like lesions, erythema annulare centrifugum-like lesions, and reticulate erythrokeratoderma. Herein, we report a rare case of EEC with associated palmoplantar keratoderma, the association which has not been described in previous reports.